Evaluating effective interventions for dyslexic children: Insights and future directions from a systematic literature review - Hayati, Rahma; Iswara, Prana Dwija; Muqodas, Idat; Yuliani, Adit (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2024)
Dyslexia is a disorder in the left brain's nervous system, which is crucial for identifying strephosymbolia to process meaning that will be used for reading, writing, and communication. Although dyslexia is a disorder that hinders normal learning processes, various interventions can be done to address the disorder. The purpose of this research is to provide a comprehensive understanding to researchers, prospective researchers, parents, and experts about the methods, measures, subjects, and approaches used by previous researchers related to interventions that can be given to dyslexic children. The focus of this research is on significant improvement and intelligent adaptation for future research design. This article adopts a qualitative approach with the Systematic Literature Review (SLR) research method. A literature review serves as the initial foundation to assist further research in the future to find information related to the topic to be studied and to avoid errors and benefit from their experience. The database used in the literature search is Harzing's Publish or Perish with online database sources from Google Scholar and Scopus. The search was done using several keywords in Indonesian and English separately, including 1) "Disleksia and Intervensi," and 2) "Dyslexia and Intervention." The search yielded 140 articles. After selection, coding, extraction, and analysis, only 13 articles met the criteria for analysis using the SLR method. All articles discussing this issue have a positive impact on addressing the disorders experienced by people with dyslexia. Proper management and continuous treatment processes are key to successfully implementing interventions. The findings imply that successful dyslexia interventions require a tailored approach that considers each child's unique needs and response to treatment. Furthermore, this study highlights the need for ongoing support and adaptive strategies to ensure the long-term effectiveness of these interventions, thereby enabling children with dyslexia to achieve improved literacy and communication skills over time.